Racial differences in platelet serotonin polymorphisms in acute coronary syndrome. Issue 200 (April 2021) - Williams, Marlene S.; Yanek, Lisa; Ziegelstein, Roy C.; McCann, Una; Faraday, Nauder
Abstract: Introduction: Genetic differences between races have been hypothesized to contribute to differences in outcome from acute coronary syndromes (ACS). Our objective was to assess racial differences in genetic variations in the platelet serotonin transporter (5HTT) and receptor in patients with ACS. Materials and methods: 127 consecutive patients, African Americans (AA) = 27; Caucasian (C) =100, admitted with ACS were evaluated for platelet function by serotonin (5HT) induced platelet activation. All patients were genotyped for two polymorphisms in the serotonin-transporter-linked polymorphic region (5-HTTLPR) S/L and LG /LA and one polymorphism of the serotonin 2A receptor (5-HT2A, T102C) gene. All patients were followed for major and minor adverse cardiac events at 12 months. Results: AA when compared to C had a lower prevalence of the HTTLPR S allele (21% vs 45%, p = 0.0003) and a higher prevalence of the LG allele (24% vs 4.5%, p = 0.0001). Allelic frequency of the 5-HT2A T102C allele was not significantly different between the races. Platelet activation was lower in AA compared to C, median EC50 5HT was 12.08 μg vs 2.14 μg ( p = 0.001). The 5-HTTLPR and the 5-HT2A polymorphisms were not associated with platelet functional responses to serotonin. There were no significant differences in major or minor adverse cardiac events in patients with serotonin transporter or receptor polymorphisms. Conclusion: We found a lower prevalence of the S allele and a higher prevalence of the G allele in AA with ACS. We also found decreased platelet activation in AA which did not correlate with serotonin-related platelet polymorphisms. It is unclear if other contributing factors may explain these platelet functional differences. Highlights: Genetic differences are hypothesized as factors contributing to ACS outcomes in African Americans African Americans have significant differences in allele frequency of the platelet serotonin transporter Decreased platelet activation in response to serotonin in African Americans is not related to serotonin polymorphisms Alternative contributing factors may explain platelet serotonin response in African Americans